Weiterempfehlungsprogramme: Die Wirkung des Akquisitionskanals und der Prämienaufteilung auf den Erfolg von Weiterempfehlungen - Klopfer, Lisa-Marie; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2020)
Referral programs are established as a marketing tool in the insurance industry, as they offer an effective and cost-efficient alternative to traditional methods of customer acquisition and retention, such as direct marketing. Previous research on referrals and referral reward programs primarily focused on the referral likelihood of existing customers. However, successful referrals also require the willingness of the recipient to accept the referral. This empirical study therefore focuses on the referral recipient and the determinants of referral acceptance. The results reveal that customers who have been acquired through a company’s referral reward program (acquisition channel) generate a higher likelihood of successful referral compared to customers acquired through other marketing activities (e.g. direct marketing). Furthermore, sharing the referral reward between sender and receiver of the referral leads to a higher likelihood of successful referral than rewarding the referrer only (reward allocation). This effect is mediated by the perceived fairness of the reward allocation.
CRIS-Team Scopus Importer:2020-07-10